Mitigating Role of Quercetin Against Cyclophosphamide-Induced Lung Injury in Rats - A. Asry, Nora (Journal of Food and Pharmaceutical Sciences, 2014)
Quercetin (Qur), a polyphenolic flavonoid compound present in large amounts in vegetables and fruits, plays important roles in human health through its antioxidant activity. This study was conducted to investigate the possible modulatory effect of Qur against cyclophosphamide (CP)-induced lung oxidative damage and to highlight the underlying mechanisms of such effect. Male Sprague-Dawely rats were divided into four groups. Group I was control. Group II received Qur (100 mg/kg/d. p.o.) for 14 consecutive days. Group III was injected once with CP (150 mg/kg, i.p.). Group IV received Qur for 7 consecutive days, before and after CP injection.Â A single i.p. injection of CP markedly increased the level of serum biomarkers; total protein, LDH. Cyclophosphamide significantly increased the lung content of lipid peroxides and decreased levels of reduced glutathione. Treatment of rats with Qur for 7 days prior to and 7 days after cyclophosphamide significantly ameliorated the alterations in lung and serum biomarkers associated with inflammatory reactions. Moreover, Qur attenuated the secretion of pro-inflammatory cytokine, TNF-Î± in rat serum. In addition, Qur slightly ameliorated CP-induced histopathological changes in lung tissue.Â Our results suggest that Qur produces a protective effect against CP-induced lung injury and suggest a role of oxidative stress and inflammation in the pathogenesis.